Researching Networked Learning: Critically Reviewing an Adaptive Evaluation - Aspden, Liz; Helm, Paul (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes the process of evaluating a large-scale e-learning implementation at a UK university. It begins by outlining the context in which the evaluation is taking place, before reviewing the approach taken and methods used. The paper then evaluates the methods and methodologies, and discusses how the instruments used could be adapted and applied to researching a variety of networked learning situations.